140k views
4 votes
Need help with this please show all work so I can learn fully

Need help with this please show all work so I can learn fully-example-1

1 Answer

6 votes

Answer: n = 5m/(1 + m)

Step-by-step explanation:

The given equation is

m = n/(5 - n)

To solve for n, the first step is to cross multiply. We have

m(5 - n) = n

We would expand the parentheses on the left by multiplying each term inside with the term outside. It becomes

5m - mn = n

Adding mn to both sides, it becomes

5m - mn + mn = n + mn

5m = n + mn

on the right, n is a common factor of n and mn. By factorizing n, we have

5m = n(1 + m)

Dividing both sides of the equation by (1 + m), it becomes

5m/(1 + m) = n(1 + m)/(1 + m)

5m/(1 + m) = n

n = 5m/(1 + m)

User Jamie Cook
by
5.0k points